Changes in the teaching career and the professional development in the Federal Institutes: advance and setbacks (Research, Society and Development, 2018)
The professional Education (PE) it comes winning visibility, against implementation of a broad set of educational reforms and the creation of several public policies and governmental programs. Among the various actions of the Federal Government in relation to this modality of education, finds itself the expansion of the Federal Network of Professional Scientific and Technological Education (FNPSTE), which has evolved so much of form quantitative as well as qualitative with the authorization of the creation of the Federal Institutes (IF). With the new institutionality of the IF, came some others changes in concerning teaching federal career. Therefore, the goal of this research is to analyze the changes in the teaching career, after the creation and expansion of the IF, allowing recognize of the advances and setbacks, in order to understand if these changes contributed positively to the professional development of teachers. For this its realized a descriptive research of documentary and bibliographic character by means of a qualitative approach with a predominance of data treatment through historical interpretation. We discuss the theme by having as basis of explanation the dialectical historical materialism. This research dialogues with several authors who talk about the FI, as Silva (2009), about the career in the FIs, Dominik (2017), Rangel and Canello (2012), and about teacher training and your professional development, García (1999) and Imbernón (2011, 2016). Its concludes, therefore, that the Law that restructures the teaching career of the FI equates, to a certain way, the teachers of the EBTT career with the of superiors Teaching, in addition that. its check too that the mentioned career gives opportunity for that them will ascend, in view of which them are stimulated to professional qualification (masters and doctorates) and have structures that encourage the participation in the research and extension, but there are also several tensioning such as the transitivity of the teacher by different levels and modality of teaching, simultaneously.